Management of Non-Vital Teeth Discoloration with the Internal Bleaching : A Case Report - Dewi Fitria Anugrahati1 , Rizky Ernawati1 , Windi Irsya1 , Yulianti Kartini Sumur1, Sukaton2 , Kun I (Institute of Medico-legal Publications Pvt Ltd, 2021)
Tooth discoloration due to intra coronal bleeding after trauma can cause aesthetic disturbances andappearance. Internal bleaching is a non-invasive method to restore tooth color which is performed afterendodontic treatment by placing a strong oxidizing agent in the pulp chamber. Aim of this study was toreport the success of internal bleaching procedure to restore discolored teeth due to trauma. A 44-year-oldfemale came to Conservative Dentistry Universitas Airlangga with chief complaint of the upper right insisortooth looks darker than the adjacent teeth. The patient had fallen 10 years ago from her motorcycle and hertooth had been painful and then the pain disappeared. In intra oral clinical examination, it showed that tooth11 had discoloured, vitality test of tooth 11 showed no response to electric pulp test. Radiographic viewshowed that radiolucen in periapical area and no fracture was found. At the first visit, treatment of singlevisit root canal using rotary instrument and gave dressing calcium hydroxide. A week later on the secondvisit, internal bleaching with hydrogen peroxide 35% was done. After bleaching, calcium hydroxide wasapplied to neutralize the oxidizing agent and then re-evaluated for the color. At the third visit, it showed thatthe tooth colour was obtain as desire from C3 to A3 (Vitapan Classical). The internal bleaching procedureon the traumatized tooth was the best option to restore the function and aesthetics according to the originaltooth colour and also provided benefits in terms of saving time, lower price, and maximum results.